Optimal Search with Costly Recall - Maarten C.W. Janssen; Alexei Parakhonyak (Tinbergen Institute, 2007)
This paper builds a consumer search model where the cost of going back to stores already searched is explicitly taken into account. We show that the optimal search rule under costly recall is very different from the optimal search rule under perfect recall. Under costly recall, the optimal search behaviour is nonstationary and, moreover, the reservation price is not independent of previously sampled prices. We fully characterize the optimal search rule under costly recall when a finite number of firms draws price quotes from a given distribution.
Keywords: C61; D11; D83; 330; Search; Costly Recall; Konsumentenverhalten; Informationskosten; Suchtheorie; Theorie